1993
DOI: 10.2134/agronj1993.00021962008500030024x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification Inhibitor Influences on Potato

Abstract: Nitrification inhibitors may reduce loss of fertilizer N from the root zone by reducing leaching and denitrification. This reduced N loss should be reflected in increased crop yields. These studies were con· ducted to determine if potato yield, specific gravity, or leaf N at flow· ering would be increased by use of nitrification inhibitors. Nitrification inhibitors dicyandiamide (DCD) and 2-chloro-6-(trichloromethyl)· pyridine (nitrapyrin) were evaluated in five studies on potato (So· Ianum tuberosum L. cv. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
4
15
1
3
Order By: Relevance
“…This is somewhat similar to the data of Martin et al (1993), where they only observed an inhibitor effect on specific gravity in 1 of 5 site-years; however, in the significant year, they saw a decrease in specific gravity as inhibitor rate increased. As with the Martin et al (1993) data, our data do not follow the suggestion of Westermann and Kleinkopf (1985) that treatments which increase yields tend to decrease specific gravity as 1984 was the only year we saw a positive yield increase from inhibitor use.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This is somewhat similar to the data of Martin et al (1993), where they only observed an inhibitor effect on specific gravity in 1 of 5 site-years; however, in the significant year, they saw a decrease in specific gravity as inhibitor rate increased. As with the Martin et al (1993) data, our data do not follow the suggestion of Westermann and Kleinkopf (1985) that treatments which increase yields tend to decrease specific gravity as 1984 was the only year we saw a positive yield increase from inhibitor use.…”
Section: Resultssupporting
confidence: 88%
“…The use of DCD did not affect total yield in 1986. These sporadic benefits to inhibitor use on potato yield are similar to the results of Roberts (1979) where response was seen in 2 of 3 years and Martin et al (1993) where they only saw a benefit in 1 of 5 site years.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Due to ignorance of the NO 3 −1 assimilation in soil microbial communities, the net nitrification rates were greatly underestimated (Stark and Hart, 1997). Reports on nitrification and denitrification are rich in the agricultural ecosystem (Martin et al, 1993;Rochester et al, 1996;Shi and Norton, 2000;Schjønning et al, 2003), however, scarce in the forest ecosystem, especially on the dynamic process along restoration or succession of forest ecosystem (Davidson et al, 1992;Zou et al, 1992;Carmosini et al, 2002). Furthermore, there are obviously different results on the dynamic properties of nitrification along forest succession: Rice and Pancholy (1972) reported that nitrification decreased in the course of succession, Davidson et al (1992) showed that the gross nitrification rates were not different between the young and old stages of forest succession, and Zou et al (1992) concluded that the old-growth forest tended to have higher gross nitrification rates than the early-successional one after studying the forest soils in the Caribbean lowland in northeastern Costa Rica.…”
Section: Introductionmentioning
confidence: 99%